2016
DOI: 10.3310/hta20080
|View full text |Cite
|
Sign up to set email alerts
|

Automated imaging technologies for the diagnosis of glaucoma: a comparative diagnostic study for the evaluation of the diagnostic accuracy, performance as triage tests and cost-effectiveness (GATE study)

Abstract: BackgroundMany glaucoma referrals from the community to hospital eye services are unnecessary. Imaging technologies can potentially be useful to triage this population.ObjectivesTo assess the diagnostic performance and cost-effectiveness of imaging technologies as triage tests for identifying people with glaucoma.DesignWithin-patient comparative diagnostic accuracy study. Markov economic model comparing the cost-effectiveness of a triage test with usual care.SettingSecondary care.ParticipantsAdults referred fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 41 publications
1
48
0
2
Order By: Relevance
“…As technologies improve, it will be important to study methods of providing cost-effective solutions for the teleophthalmic management of visually impairing eye conditions including using machine learning approaches for image processing. A recent study evaluating the cost-effectiveness of automated imaging in glaucoma diagnosis found a composite triage test involving imaging test, IOP and visual acuity measurements to be cost-effective compared with clinical examination 43. Furthermore, all studies in our review (except for one) were conducted in developed countries in North America and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…As technologies improve, it will be important to study methods of providing cost-effective solutions for the teleophthalmic management of visually impairing eye conditions including using machine learning approaches for image processing. A recent study evaluating the cost-effectiveness of automated imaging in glaucoma diagnosis found a composite triage test involving imaging test, IOP and visual acuity measurements to be cost-effective compared with clinical examination 43. Furthermore, all studies in our review (except for one) were conducted in developed countries in North America and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…A complete description of the patients’ enrolment and flow in the GATE study has been previously published 11. A flow diagram of participants included in this study is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The GATE study11 found OCT sensitivity was 0.77 and specificity was 0.79 for diagnosing manifest glaucoma using the Spectralis RNFL classification of outside normal limits. Combination of two different imaging tests did not improve substantially the diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available methods for evaluating malignant disease transitions, such as courses and outcomes, include the Markov model 5. The Markov model is employed in health economics6 and disease treatment evaluations,7 as well as in the glaucoma field to determine gain and loss of treatment costs,8 perform automated diagnoses using imaging technologies,9 and assess imaging-based progression 10. However, few studies have reported on this model for clinical course evaluation in VFD 11.…”
Section: Introductionmentioning
confidence: 99%